Impact of Uncontrolled Hypertension at 3 Months After Intracerebral Hemorrhage - Alessandro Biffi; Kay‐Cheong Teo; Juan Pablo Castello; Jessica R. Abramson; Ian Y. H. Leung; William C. Y. Leung; Yujie Wang; Christina Kourkoulis; Evangelos Pavlos Myserlis; Andrew D. Warren; Jonathan Henry; Koon‐Ho Chan; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Survivors of intracerebral hemorrhage (ICH) are at high risk for recurrent stroke, which is associated with blood pressure control. Because most recurrent stroke events occur within 12 to 18 months of the index ICH, rapid blood pressure control is likely to be crucial. We investigated the frequency and prognostic impact of uncontrolled short‐term hypertension after ICH. Methods and Results We analyzed data from Massachusetts General Hospital (n=1305) and the University of Hong Kong (n=523). We classified hypertension as controlled, undertreated, or treatment resistant at 3 months after ICH and determined the following: (1) the risk factors for uncontrolled hypertension and (2) whether hypertension control at 3 months is associated with stroke recurrence and mortality. We followed 1828 survivors of ICH for a median of 46.2 months. Only 9 of 234 (4%) recurrent strokes occurred before 3 months after ICH. At 3 months, 713 participants (39%) had controlled hypertension, 755 (41%) had undertreated hypertension, and 360 (20%) had treatment‐resistant hypertension. Black, Hispanic, and Asian race/ethnicity and higher blood pressure at time of ICH increased the risk of uncontrolled hypertension at 3 months (all P<0.05). Uncontrolled hypertension at 3 months was associated with recurrent stroke and mortality during long‐term follow‐up (all P<0.05). Conclusions Among survivors of ICH, >60% had uncontrolled hypertension at 3 months, with undertreatment accounting for the majority of cases. The 3‐month blood pressure measurements were associated with higher recurrent stroke risk and mortality. Black, Hispanic, and Asian survivors of ICH and those presenting with severe acute hypertensive response were at highest risk for uncontrolled hypertension.